Identification students’ misconception using four-tier diagnostic test on Newton Law subject - Sundaygara, C; Gusi, L A R P; Pratiwi, H Y; Ayu, H D; Jufriadi, A; Hudha, M N (Journal of physics. Conference series, 2021)
Misconception is something that causes students fail to understand physics concept intensively. The research aims to identify the students’ misconception on Newton Law concept using four-tier diagnostic test. Method used in the research was descriptive method. Data of students’ misconception was collected using test and interview. The subjects of the research were students of X MIPA 5 in State Senior High 10 Malang in 2019/2020 academic year and they were 32 students. The result of the research shows that the level of students’ misconception of X MIPA 5 in State Senior High 10 Malang is 54% which belongs to medium category. The research found that the misconception which happened to most students was on Newton II Law which is 63%. It also relevead that misconception in students occur because of experiences or events experiences by students in everuday life, students’ initial concepts and teachear teaching methods.